2021
DOI: 10.3390/cancers13010156
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Diagnostic Intervals as Marker of Missed Diagnostic Opportunities in Bladder and Kidney Cancer Patients with Alarm Features: A Longitudinal Linked Data Study

Abstract: Background: In England, patients who meet National Institute for Health and Care Excellence (NICE) guideline criteria for suspected cancer should receive a specialist assessment within 14 days. We examined how quickly bladder and kidney cancer patients who met fast-track referral criteria were actually diagnosed. Methods: We used linked primary care and cancer registration data on bladder and kidney cancer patients who met fast-track referral criteria and examined the time from their first presentation with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Details of data acquisition and cohort identification have been described in previous studies. 17 , 29 Data on patients aged ≥25 years who were diagnosed with bladder and renal cancer between April 2012 and December 2015 were extracted from the CPRD. These data were linked at source to the cancer registry, from which additional patients were identified using International Classification of Diseases, Tenth Revision (ICD-10) cancer codes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of data acquisition and cohort identification have been described in previous studies. 17 , 29 Data on patients aged ≥25 years who were diagnosed with bladder and renal cancer between April 2012 and December 2015 were extracted from the CPRD. These data were linked at source to the cancer registry, from which additional patients were identified using International Classification of Diseases, Tenth Revision (ICD-10) cancer codes.…”
Section: Methodsmentioning
confidence: 99%
“… 17 , 25 , 28 Each patient’s index abnormal test was defined as the first abnormal test within the 12-month period before diagnosis, concordant with prior literature. 17 , 29 …”
Section: Methodsmentioning
confidence: 99%
“…A prolonged primary care interval (from patient presentation to referral) is associated with worse clinical outcomes [4,5]. Currently, in England, median diagnosis time for bladder and kidney cancer -after presentation in primary care with a relevant clinical feature -is 51 and 70 days respectively, with variation seen by symptom [6]. Visible haematuria is present in the majority of patients with bladder cancer (53%), however, it is less common in individuals diagnosed with kidney cancer (18%) [7].…”
Section: Background and Aimsmentioning
confidence: 99%
“…While 5.1% of people with VH in a primary care setting are ultimately diagnosed with urological cancers, the positive predictive value (PPV) of NVH is less certain and may be as low as 1.6% in primary care [7]. The focus on haematuria may impede early identification of cancers that present atypically or with a number of non-specific symptoms [6,9]. This could also lead to the over-referral of lower risk individuals presenting with haematuria [10].…”
Section: Background and Aimsmentioning
confidence: 99%
“…Globally, this condition affects approximately 150 million people each year, resulting in approximately 3.5 billion dollars in health costs (Dıáz et al, 2020). Furthermore, UTIs can cause serious sequelae, including frequent recurrences, pyelonephritis with sepsis, renal damage in young children, pre-term birth in pregnant women, and complications caused by the frequent use of antimicrobial drugs, including high-level antibiotic resistance (Flores-Mireles et al, 2015;Karavanaki et al, 2019;Rousham et al, 2019;Zhou et al, 2021). Previous research has shown that the focus of infection in 20-30% of all patients with sepsis is localized in the urogenital tract and that urosepsis may cause mortality rates of 25% to 60% in certain patient groups (Wagenlehner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%